Special legal solutions in a field of the State Treasury guarantees in 2020–2022 – the problem of controlling an amount of potential liabilities - Małgorzata Cilak (Prawo Budżetowe Państwa i Samorządu)
The subject of the article is an analysis of State Treasury guarantees granted in the years 2020–2022 in the context of covering these liabilities with debt growth limits determined annually in the Budget Act. The conclusion will be presented that liabilities arising from guarantees of the State Treasury constitute an element of state public debt in the light of Article 216(5) of the Constitution of the Republic of Poland. Their amount should therefore be controlled by the competent public authorities, in particular the Parliament and the Council of Ministers. An expression of parliamentary control over the amount of state public debt resulting from the guarantees granted by the State Treasury is the requirement for the Budget Act to specify the limit up to which they may be granted. The practice of not including certain guarantees granted under special acts passed in 2020–2022 into budget limits reduces parliamentary control over the amount of these liabilities. State budget implementation reports for 2020–2022 show that State Treasury guarantees not included in the limit specified in the Budget Act constituted a significant part of State Treasury guarantees granted in total in this period.